2008
DOI: 10.1111/j.1556-4029.2008.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Age Estimation from the Human Os Coxa: A Test on a Documented Italian Collection*

Abstract: Current standards for age at death estimation from the pelvis are based on Americans of European and African ancestry. Our limited understanding of population variability hampers our efforts to apply these techniques to the various skeletal populations around the world, especially in global forensic contexts. However, documented skeletal samples are rare, limiting our ability to test our techniques. This study tested the Suchey-Brooks pubic symphysis aging method and the auricular surface method originally dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
85
2
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 13 publications
10
85
2
2
Order By: Relevance
“…Saunders et al [4] used a small, documented population from Belleville, Ontario and reported overall agreement with Lovejoy et al [24], but the reliability of the method decreased after age 45. On Portuguese and Italian individuals, Santos [21] and Hens and colleagues [10] found similar results. Using the Grant collection at the University of Toronto, Bedford and colleagues [27] found that the auricular surface method overestimated the ages of younger individuals and underestimated the ages of individuals over 50 by as much as 5-10 years.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…Saunders et al [4] used a small, documented population from Belleville, Ontario and reported overall agreement with Lovejoy et al [24], but the reliability of the method decreased after age 45. On Portuguese and Italian individuals, Santos [21] and Hens and colleagues [10] found similar results. Using the Grant collection at the University of Toronto, Bedford and colleagues [27] found that the auricular surface method overestimated the ages of younger individuals and underestimated the ages of individuals over 50 by as much as 5-10 years.…”
Section: Introductionsupporting
confidence: 71%
“…The Suchey-Brooks reference sample is large and includes a number of modern North American ethnic groups. However, despite its popularity, pubic symphyseal age assessment has not performed well in validation studies outside the U.S, including those based on modern French autopsied individuals [20], Canadian pioneers [4], and modern Portuguese and Italian individuals from cemetery collections [10,21]. These studies have demonstrated biased age estimates and difficulty in determining the age of individuals over 35 years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on estimation methods for the age of adult skeletons is still a developing area in both fields. It is now well established that inter-individual variability of age-related bone changes are caused by a complex interaction between many factors, and that the observed pattern may be different depending on the population under study [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%